Characterization of the Complete Nucleotide Sequences of mcr-1-Encoding Plasmids From Enterobacterales Isolates in Retailed Raw Meat Products From the Czech Republic - Zelendova, Marketa; Papagiannitsis, Costas C.; Valcek, Adam; Medvecky, Matej; Bitar, Ibrahim; Hrabak, Jaroslav; Gelbicova, Tereza; Barakova, Alzbeta; Kutilova, Iva; Karpiskova, Renata; Dolejska, Monika (Frontiers in Microbiology, 2021)
The aim of our study was to determine complete nucleotide sequence of mcr-1-carrying plasmids from Enterobacterales isolates recovered from domestic and imported raw retailed meat and compare them with plasmids available at the GenBank sequence database. A set of 16 plasmids originating from Escherichia coli (n=13), Klebsiella pneumoniae (n=2) and Citrobacter braakii (n=1) were analysed. In our previous study, data from whole genome sequencing showed that mcr-1 gene was located on plasmids of different incompatibility groups (IncHI2, IncI2 and IncX4). The IncI2 (n=3) and IncX4 (n=8) plasmids harboured mcr-1.1 gene only, whereas IncHI2 sequence type 4 plasmids (n=5) carried large multidrug resistance (MDR) regions. MDR regions of IncHI2 plasmids included additional antimicrobial resistance genes conferring resistance to β-lactams (blaTEM-1), aminoglycosides [aadA1, aadA2 and aph(6)-Id], macrolides [mef(B)], tetracycline (tetA, tetR) and sulphonamides (sul1, sul2 and sul3). Likewise, IncHI2 plasmids carried several insertion sequences including IS1, IS3, IS26, IS1326 and ISApl1. In conclusion, our findings confirmed the involvement of IncX4, IncI2 and IncHI2 plasmids in the dissemination of mcr-1.1 gene in several environmental niches, as in samples of retail meat originating from different geographical regions. In contrast to IncX4 and IncI2, IncHI2 plasmids were more diverse and carried additional genes for resistance to heavy metals and multiple antimicrobials.